Role of laboratory markers in predicting severity of acute appendicitis - Samarth Virmani; Padubidri Santosh Prabhu; P T Sundeep; Vijay Kumar (Wolters Kluwer Medknow Publications, 2018)
Background: Accurately differentiating simple and complicated acute appendicitis (CAA) in children preoperatively can be challenging. The aim of this study is to evaluate the ability of the neutrophil-to-lymphocyte ratio (NLR), total leukocyte count (TLC), percentage lymphocyte, and percentage neutrophil counts to predict the type of appendicitis a patient has preoperatively and to determine the better indicator among these. Materials and Methods: Record of 233 patients under 18 years of age who underwent appendectomy from 2005 to 2014 was evaluated. Based on perioperative findings of the surgeon, the patients were grouped under categories simple acute appendicitis (SAA) and CAA. Information such as age, gender, and laboratory investigations of the patients were recorded and analyzed. Results: SAA included 185 patients and CAA included 48 patients. An NLR >4.8, TLC >13,500 cells/mm3, percentage lymphocyte count <14.8%, and percentage neutrophil count >75% were found to be associated with complicated appendicitis. The highest sensitivity and specificity among these findings were found with the percentage lymphocyte count, which were 70.8% and 63.8%, respectively. Conclusion: The preoperative percentage lymphocyte count serves as a better indicator than TLC, NLR, and percentage lymphocyte count and is a useful parameter in differentiating simple and complicated appendicitis and can be used as a valuable adjunct to the surgeon's clinical evaluation.